Local Government Efforts in Realizing Gender Responsive Regional Policies in Banyumas District - Riris Ardhanariswari; Tenang Haryanto; Manunggal KW; Siti Kunarti (Jambe Law Journal, 2021)
The international community has come to an agreement on the importance of gender issues to solve such problems as the gender inequality, the gap between men and women. Gender issues have become a part of the national direction and strategy in carrying out national development. Therefore, addressing these issues has to be integrated in various national policies. The central government has granted authorities to each region in Indonesia to make gender-responsive regional policies, hoping that the concept of justice and gender equality in Indonesia be realized properly. This study uses a normative legal method by examining secondary data normatively such as laws and regulations, research papers on policy gender-responsive regional development. This article was originally a research focusing on the Government of Banyumas Regency in creating a gender-responsive regional policy. Through Banyumas Regent Regulation Number 35 of 2018 concerning Guidelines for Implementation of Gender Mainstreaming, the Banyumas Regency Government has supported gender responsive regional policies.